2022
DOI: 10.1155/2022/8131531
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Mechanism of Gegen Qinlian Decoction Regulating ABTB1 Expression in Colorectal Cancer Metastasis Based on PI3K/AKT/FOXO1 Pathway

Abstract: It was to investigate the role of Gegen Qinlian decoction (GQD) in the regulation of ABTB1 gene based on PI3K/AKT/FOXO1 signaling pathway in colorectal cancer (CRC) metastasis. In this study, 10 cases of the CRC mouse model were established by inoculating CT26 cells into the spleen of mice, which were divided into the experimental group and the control group, 5 cases in each group; the control group was intragastrically administered with normal saline 0.3 mL/d, and the experimental group was intragastrically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…We also investigated the gene expression characteristics of MCM2 which presented a high mutation rate, indicating that MCM2 may be a potential marker for diagnosing various cancers. We found the top-10 gene that was co-mutated with MCM2, which have been reported in multiple cancers, such as colorectal cancer ( Li et al, 2022 ), BRCA ( Lin et al, 2020 ), LUAD ( Zhang et al, 2020 ) and LIHC ( Li et al, 2021a ). Furthermore, we integrated MCM2 in the GGI and PPI networks and found that it was strongly associated with genes and proteins related to the cell cycle and DNA replication, such as the CDC family, a group of genes coding proteases and phosphatases that regulate the cell division phase and cell cycle, and POLA1, a protein contributing to the DNA replication pathway.…”
Section: Discussionmentioning
confidence: 74%
“…We also investigated the gene expression characteristics of MCM2 which presented a high mutation rate, indicating that MCM2 may be a potential marker for diagnosing various cancers. We found the top-10 gene that was co-mutated with MCM2, which have been reported in multiple cancers, such as colorectal cancer ( Li et al, 2022 ), BRCA ( Lin et al, 2020 ), LUAD ( Zhang et al, 2020 ) and LIHC ( Li et al, 2021a ). Furthermore, we integrated MCM2 in the GGI and PPI networks and found that it was strongly associated with genes and proteins related to the cell cycle and DNA replication, such as the CDC family, a group of genes coding proteases and phosphatases that regulate the cell division phase and cell cycle, and POLA1, a protein contributing to the DNA replication pathway.…”
Section: Discussionmentioning
confidence: 74%
“…), Huang Qin ( Scutellaria baicalensis Georgi), Huang Lian ( Coptis chinensis Franch.) CT-26 spleen transplanted mice Proliferation ↓, Migration ↓ ↑: p-PI3K, p-AKT, p-FOXO1, ABTB1 PI3K/AKT/FOXO1 [ 55 ] Tounong Powder extracts (TNSEs) Huang Qi ( Astragalus membranaceus (Fisch. )), Dang Gui ( Aaugellica sinensis (Oliv) Diels.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 55 ] found that Gegen Qinlian Decoction (GQD) could inhibit CT-26 CRC growth accompanied by upregulation of p-PI3K, p-Akt, phosphorylated forkhead box transcription factor O1 (p-FOXO1), and ankyrin repeat and BTB/POZ domain containing protein 1 (ABTB1). Fang et al [ 56 ] found that Tounong powder extracts (TNSEs) induced LoVo cell growth inhibition in a dose- and time-dependent manner; significantly downregulated the expression of PI3K, p-AKT, phosphorylated mechanistic target of rapamycin (p-mTOR), and p-p70s6k1; and upregulated the expression of cleaved caspase-9 and -3.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%